Pengaruh Kompetensi dan Motivasi Kerja Terhadap Kinerja Pegawai pada Kantor Dinas Perpustakaan dan Kearsipan Kabupaten Enrekang - Wanda Azisa; Agung Widhi Kurniawan; Burhanuddin Burhanuddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Employee performance plays a crucial role in achieving an organization’s goals. It is closely linked to the effects of work competence and work motivation. Recognizing this relationship, companies should focus on these factors to ensure that employee performance remains at an optimal level, thereby facilitating the attainment of the company’s iobjectives. iThis istudy iaims to: (1) iassess whether work competence has a partial ieffect on employee aperformance at the iEnrekang Regency Library and Archives Office; (2) evaluate whether work motivation has a partial effect on employee performance at the same office; and (3) examine whether work competence and work motivation together have a significant impact on employee performance at the Enrekang Regency Library and Archives Office. The population for this research consisted of all employees at the Enrekang Regency Library and Archives Office, totaling 58 individuals. The study utilized a quantitative research approach, surveying the entire population of 58 employees. Data collection was conducted through the distribution of questionnaires. The variables included in this research are employee performance (Y) as the dependent variable, with work competence (X1) and work motivation (X2) serving as independent variables. For data analysis, multiple linear regression was employed, utilizing iStatistical Product iand iService iSolution (SPSS) iversion 23. The ifindings irevealed ithat: (1) work icompetence ihas a ipositive iand isignificant ipartial ieffect on iemployee performance at the iEnrekang iRegency iLibrary iand iArchives iOffice; (2) work motivation ialso ihas a ipositive and isignificant ipartial ieffect on iemployee performance at ithe isame ioffice; iand (3) iboth iwork icompetence and iwork imotivation itogether have a ipositive iand isignificant iimpact on iemployee iperformance at the Enrekang Regency iLibrary iand iArchives iOffice.